A mercantilist approach to the chinese economic growth (2022)
This paper studies the short-run and long-run relationships between trade, investment, and the Chinese economic growth from 1992 to 2019. A vector error correction (VEC) model was estimated in order to analyze the causal relationships among balance of trade, investment (both national and foreign), and economic growth. The results helped us to discuss the mechanisms considered within the mercantilist literature to relate a positive balance of trade and economic growth. Particularly, the estimation suggests that the causality mechanism between the variables is closer to a financial mercantilist or developmental explanation or rather than a monetarist mercantilist approach. That is, the positive effect of the commercial balance on economic growth in China seems related to the increase of national investment, instead of the attraction of foreign direct investment.